2020
DOI: 10.1590/1516-4446-2019-0783
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in suicidal ideation and associated factors among adolescents

Abstract: Objectives: Suicide is one of the leading causes of death in adolescence, and the second most common cause of death among young people. The objective of this study was to identify trends in suicidal ideation by sex and ascertain factors associated with this outcome. Methods: Secular trend study with statewide coverage conducted at 5-year intervals, with 4,207 adolescents (2006), 6,264 adolescents (2011) and 6,026 adolescents (2016). Logistic regression was used to evaluate the secular trend of suicidal ideatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
0
4
0
13
Order By: Relevance
“…In the study performed in the Netherlands, the prevalence of reported suicide attempts during the past 12 months decreased from 2.9% during 2010–2011 to 1.9% during 2014–2015 [ 32 ]. A Brazilian study found that there was no trend in the prevalence of suicidal ideation in adolescents from 2006 to 2011, but a significant upward trend was identified in the 2016 survey in comparison to the previous surveys [ 33 ]. In general, the comparability of suicide data between countries could be affected by a number of factors, including the time horizon of the analysis and methods of data collection.…”
Section: Discussionmentioning
confidence: 99%
“…In the study performed in the Netherlands, the prevalence of reported suicide attempts during the past 12 months decreased from 2.9% during 2010–2011 to 1.9% during 2014–2015 [ 32 ]. A Brazilian study found that there was no trend in the prevalence of suicidal ideation in adolescents from 2006 to 2011, but a significant upward trend was identified in the 2016 survey in comparison to the previous surveys [ 33 ]. In general, the comparability of suicide data between countries could be affected by a number of factors, including the time horizon of the analysis and methods of data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Ressalta-se que o conflito com os amigos e a falha no suporte social constitui fatores de risco associados à ideação suicida (Soares et al, 2020), os adolescentes requerem ser cuidados e compreendidos (Tardivo, Rosa, Ferreira, Chaves & Pinto Júnior, 2019).…”
Section: (A47g7)unclassified
“…Nesta perspectiva, ressalta-se que a escola é cenário relevante para implementar estratégias que fortaleça a rede de apoio social e a redução de comportamento suicida (Soares et al, 2020), além de favorecer o desenvolvimento de habilidades que contribuam para o enfrentamento positivo e o gerenciamento das emoções (Fonseca, Silva, Araújo & Botti, 2018).…”
Section: (A47g7)unclassified
“…Apesar do silêncio social e do distanciamento profissional sobre o suicídio de crianças e adolescentes, o cenário clínico-epidemiológico pediátrico atual no Brasil e no mundo encontra-se fortemente marcado pela morbimortalidade por causas externas e pela crescente prevalência de transtornos mentais [12][13][14] . Dados nacionais corroboram a tendência de crescimento na prevalência de ideação suicida e na incidência de suicídio na população de 10 a 19 anos, principalmente se considerado o subgrupo de 15 a 19 anos [15][16][17] . Tendo como referência o diverso universo de adolescentes e jovens de 15 a 29 anos, tem-se o suicídio como uma das suas principais causas de morte 17,18 .…”
Section: Introductionunclassified